Leadership in the Big Bangs of European Integration - Beach, D.; Beach, D.; Mazzucelli, C.; Mazzucelli, C. (Palgrave Studies in European Union Politics,, 2006)
This book presents the first comprehensive analysis of the major treaty reforms over the past two decades, to consider whether the path from the Single European Act in 1985 to the present Constitutional Treaty has been pushed by the Franco-German tandem, or has been the result of leadership provided the Commission or smaller member states.